The Changing Limits and the Limits of Change: the state, private firms, international industry and China in the evolution of Taiwan's electronics industry. - Fuller *, Douglas B. (Journal of Contemporary China, 2005)
This paper examines the changing role of the state and private enterprise in Taiwan's electronics industry as the industry responds to growth of intra-firm capabilities and the rise of China as a manufacturing base. The industry has a sharp dichotomous outcome between the technologically strong IC sector, which has been able to create interdependence with global lead firms, and the systems manufacturing firms, which find themselves trapped in a dependent position vis-à-vis the global lead firms. Due to different positions in global value chains, the IC industry firms have been better able to create advantages out of the opportunities of new firm capabilities and China than the systems firms even as the balance of policy has shifted somewhat away from the state and towards private enterprise.